Pengaruh Literasi Finansial Berbasis Virtual Reality pada Kemampuan Berfikir Kritis Siswa - Asri Ratna Sari (Proceedings Series on Social Sciences & Humanities, 2021)
This type of research is an experimental study consisting of two classes with different treatments. This study aims to determine (1) critical thinking skills of students who are taught using virtual reality-based financial literacy, (2) critical thinking abilities of students taught using power point media-based financial literacy, (3) the effect of learning using virtual reality-based financial literacy on students' critical thinking skills. The population of this study were students of class VII B as the experimental group and class 7 A as the control group, at SMP N 2 Banjarnegara in the odd semester of the 2020/2021 school year, the sample was using the simple random sampling method. The research data were analyzed using descriptive and inferential statistical analysis techniques. The results of descriptive statistical analysis are as follows: (1) The critical thinking ability of students who are taught using virtual reality-based financial literacy is in the high category with an average of 88 with a standard deviation of 12.836601 from a maximum score of 100, (2) Critical thinking skills students taught using virtual reality-based financial literacy are at an average of 66 with a standard deviation of 15.47284289. From the results of inferential statistical analysis, Fvalue <Ftable (0.6908436214 <1.85) so that H0 is rejected or there is a significant effect of learning using virtual reality-based financial literacy on students' critical thinking skills. Observations show that students are more interested in financial literacy using virtual reality because students feel the sensation of interacting with the real environment, visualizing abstract things to be easy to understand and increasing their imagination.